Genitourinary syndrome of menopause: Should we treat symptoms or signs?. (October 2022) - Cucinella, Laura; Martini, Ellis; Tiranini, Lara; Molinaro, Pietro; Battista, Federica; Nappi, Rossella E.
Abstract: Genitourinary syndrome of menopause (GSM) is a heterogeneous chronic condition potentially affecting the quality of life (QoL) and sexual health in women at midlife and beyond. A disconnection between signs and symptoms of GSM is evident in clinical studies and everyday practice, as several psychosocial factors may modulate the clinical manifestation of urogenital atrophic changes. A symptom-oriented approach forms the basis of a tailored management, but the prevention of the progressive signs of urogenital ageing seems important in a long-term perspective promoting longevity. In this short review, main data about the effectiveness of evidence-based available treatments on different components of GSM, including vaginal, vulvar and urinary symptoms, as well as on signs of urogenital atrophy, are summarised, highlighting gaps in the literature, which should be addressed to improve evidence-based treatment individualisation. Highlights: Genitourinary syndrome of menopause (GSM) is a heterogeneous chronic condition potentially affecting the quality of life (QoL) and sexual health in midlife women. GSM is a clinical diagnosis requiring the presence of bothersome symptoms associated with signs of vulvovaginal atrophy (VVA). The most recent guidelines recommend that treatment choice should be guided by the severity of symptoms and personal risk factors. Vulvar and vaginal signs assessed by clinicians are useful to recognise and manage GSM in routine practice. Comparative data between available options will help clinicians to increase response rate, as well as improve satisfaction and long-term adherence.